2017
DOI: 10.3389/fmicb.2017.02209
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological and Physicochemical Changes in Natural Green Heat-Shocked Aloreña de Málaga Table Olives

Abstract: Preserving the highly appreciated natural freshness of Aloreña de Málaga table olives and preventing their progressive darkening during processing is a major challenge. In this work, heat-shocked (60°C, 5 min) fruits were processed according to the three denominations referred to in the Protected Designation of Origen (cured, fresh green, and traditional) and their characteristics compared with those that followed the habitual industrial process (controls). The results revealed that the effects of the heat tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 28 publications
3
14
0
Order By: Relevance
“…Lactobacillaceae was the dominant family identified in olive samples from both cultivars, indicating that these were all lactic acid fermentations, which was also verified by the classical microbiological analysis. The significant role of this microbial group in olive fermentations has been extensively reviewed by Hurtado et al [39], and it is commonly found in the microbiota of fermented green and black olives using both classical microbiological and metagenomics analyses [7,15,18,[40][41][42]. NGS highlighted relevant differences in the occurrence of different Lactobacillus species, depending on the cultivar.…”
Section: Discussionmentioning
confidence: 99%
“…Lactobacillaceae was the dominant family identified in olive samples from both cultivars, indicating that these were all lactic acid fermentations, which was also verified by the classical microbiological analysis. The significant role of this microbial group in olive fermentations has been extensively reviewed by Hurtado et al [39], and it is commonly found in the microbiota of fermented green and black olives using both classical microbiological and metagenomics analyses [7,15,18,[40][41][42]. NGS highlighted relevant differences in the occurrence of different Lactobacillus species, depending on the cultivar.…”
Section: Discussionmentioning
confidence: 99%
“…However, in order to standardize this process and consequently secure the quality of the final product, the study of microbiological and physicochemical descriptors for monitoring the fermentation is a pre-request [2]. Three styles (Spanish, Greek, and Californian) are the most well-known and established commercial types globally [3].…”
Section: Introductionmentioning
confidence: 99%
“…Despite their significant role, olives fermentation remains empirical and thus an inconstant process. In recent years, process modernization, by the use of appropriate starter cultures, has been extremely supported, aiming to the stabilization of fermentation worldwide (Rodríguez-Gómez et al, 2017).…”
mentioning
confidence: 99%